Process Improvement for Interinstitutional Research Contracting. Issue 4 (17th June 2015) - Varner, Michael; Logan, Jennifer; Bjorklund, Todd; Whitfield, Jesse; Reed, Peggy; Lesher, Laurie; Sikalis, Amy; Brown, Brent; Drollinger, Sandy; Larrabee, Kristine; Thompson, Kristie; Clark, Erin; et al.
Abstract Introduction Sponsored research increasingly requires multiinstitutional collaboration. However, research contracting procedures have become more complicated and time consuming. The perinatal research units of two colocated healthcare systems sought to improve their research contracting processes. Methods The Lean Process, a management practice that iteratively involves team members in root cause analyses and process improvement, was applied to the research contracting process, initially using Process Mapping and then developing Problem Solving Reports. Results Root cause analyses revealed that the longest delays were the individual contract legal negotiations. In addition, the "business entity" was the research support personnel of both healthcare systems whose "customers" were investigators attempting to conduct interinstitutional research. Development of mutually acceptable research contract templates and language, chain of custody templates, and process development and refinement formats decreased the Notice of Grant Award to Purchase Order time from a mean of 103.5 days in the year prior to Lean Process implementation to 45.8 days in the year after implementation (p = 0.004). Conclusions The Lean Process can be applied to interinstitutional research contracting with significant improvement in contract implementation.